PENERAPAN TALKING STICK DALAM MENINGKTAKAN PRETASI BELAJAR PADA MATA PELAJARAN SKI KELAS X DI MAMUHAMMADIYAH 7 BUNGKAL - Diyannita Ratnasari; nuraini nuraini; Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2019)
This study aims: to determine the application of learning the history of Islamic culture using the talking stick method in mam 7 bungkal ponorogo district, would like to know the results of evaluating the history of Islamic culture learning using the talking stick method and the supporting and inhibiting factors in learning the history of Islamic culture using the talking method stick This study uses Classroom Action Research (CAR) where in this study involved teachers and students in which the object of research was participants in grade X in Muhammadiyah 7 Bungkal, totaling 9 students. This study uses observation techniques, tests (pre-test and post-test) and also documentation. observations made by researchers in learning the history of Islamic culture using the talking stick method seem to have good results, seen from the results of pre-test and post-test that have increased from cycle I to cycle II. seen in the first test only gets 44% because there are only 4 people out of 9 students who have completed grades above KKM 75. while in the last test there is an increase to 75%. it can be seen from the increase in the achievements of students this can be quite successful in applying the talking stick method in the material history of Islamic culture on the subject of Arab civilization discussion before Islam.